IMPLIKASI KETIDAKTERSEDIAAN TERMINAL TIPE C TERHADAP KEBERLANGSUNGAN ANGKUTAN UMUM DI KOTA BAUBAU DALAM PERSPEKTIF PERATURAN MENTERI PERHUBUNGAN NOMOR 24 TAHUN 2021 TENTANG PENYELENGGARAAN TERMINAL PENUMPANG ANGKUTAN JALAN - La Ode Muhaimin; Nasrin; Wa ode Nurshinta Muhammad (Fakultas Hukum Universitas Dayanu Ikhsanuddin, 2026)
The background of this research is based on the absence of a Class C Terminal in Baubau City, which has caused various problems, such as irregular public transportation operations, the emergence of shadow terminals, and a decline in the efficiency and quality of public transportation services. This study aims to examine the legal and operational impacts of the absence of a Class C Terminal and to assess the suitability of the actual conditions in the field with the applicable regulatory provisions. The research method used is normative juridical, applying a statute approach and a conceptual approach. The legal sources used include primary legal materials in the form of relevant laws and regulations, as well as secondary legal materials in the form of relevant literature and scientific works. Data analysis was conducted qualitatively through the interpretation of legal norms and their application at the regional level. The results of the study show that the absence of a Class C Terminal in Baubau City has disrupted the local transportation system, weakened supervision of routes, led to the emergence of unofficial terminals (shadow terminals), and decreased public interest in using public transportation. From a legal perspective, this condition shows that the implementation of Minister of Transportation Regulation No. 24 of 2021 has not been maximized and that the role of local governments in providing transportation facilities as part of public services has not been optimal. Therefore, the construction of a Class C Terminal is urgent in order to realize a safe, orderly, efficient, and sustainable transportation system in accordance with the principles of good governance and good public service management.